Penerapan Metode Pembelajaran Eksperimen pada Pembelajaran IPA untuk Meningkatkan Keterampilan Proses Sains dan Hasil Belajar Siswa Di Kelas V SDN 009 Bengkulu Utara - Djumiati Djumiati (Journal of Elementary School (JOES), 2020)
This study aims to prove whether the application of experimental learning methods in science learning can improve students' science process skills and student learning outcomes. The research design used was classroom action research with two learning cycles. The research subjects in this study were students of class VA SD Negeri 009 Bengkulu Utara which consisted of 20 students. The research was conducted for two months starting from January 2020 to March 2020. The results showed that the experimental learning method was proven to be able to improve students 'science process skills in science learning, where in the pre-cycle phase, the percentage of students' science process skills was 25%, increasing in the cycle. I was 60% and increased in cycle II by 85%. The experimental learning method was also proven to be able to improve student learning outcomes in science learning, where in the pre-cycle phase the classical completeness level was 40%, increased in cycle I to 65% and in cycle II increased to 85%. In conclusion, the application of the experimental learning method of science learning to students of SD Negeri 009 Bengkulu Utara was effective in improving students' science process skills and student learning outcomes. Keywords: Experiment, Learning Outcomes, Science Process Skills Learning Methods